Tanggung Jawab Pelaku Usaha Skincare Atas Tindakan Penjualan Dibawah Harga Pasar - Ode, Anisa; Tjoanda, Merry; Kuahaty, Sarah Selfina (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2025)
Pricing strategy plays an important role in determining a company's position in the market. One example of an act of selling below market price. Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, stipulates that